"Influence of modifiable and non-modifiable variables on functioning in bipolar disorder: a path analytical study". (30th October 2020) - Cotrena, Charles; Damiani Branco, Laura; Milman Shansis, Flávio; Paz Fonseca, Rochele
Abstract: Functional recovery has garnered increasing attention in the literature on bipolar disorder (BD), but is still a challenge for most interventions. Additionally, the impact of modifiable and non-modifiable factors on individual functioning is still poorly understood. Objective: The aim of this study was to investigate the influence of modifiable (mood, cognitive reserve, cognitive performance) and non-modifiable factors (diagnosis, suicide attempts, substance use, age) on self-reported functioning in BD. Methods: 103 adults with no mood disorders and 95 individuals with BD completed the WHODAS 2.0, in addition to a neuropsychological battery and diagnostic assessments. Path analysis was then used to analyse the relationships between modifiable and non-modifiable predictors of functioning in the sample. Results: Cognitive reserve and age had an indirect influence on individual functioning, mediated by cognitive performance. The influence of diagnosis and depressive symptoms on functioning was partly direct, and partly mediated by cognition. The presence of psychiatric comorbidities in addition to BD also had a significant influence on individual functioning. Conclusions: Initiatives focussed on modifiable factors such as depressive symptoms and cognitively stimulating activities, which increase cognitive reserve, may be a useful complement to existing treatments and help patients achieve functional recovery. KEY POINTS: Individual functioning was influenced by cognitive performance, cognitive reserve, age, diagnosis and depressive symptoms. Executive functioning mediated the influence of age and cognitive reserve on individual functioning. Interventions focussed on depressive symptoms and cognitive stimulation may help patients achieve functional recovery.